Understanding the engagement of key decision support persons in patient decision making around breast cancer treatment. Issue 10 (11th January 2019) - Veenstra, Christine M.; Wallner, Lauren P.; Abrahamse, Paul H.; Janz, Nancy K.; Katz, Steven J.; Hawley, Sarah T.
Abstract : Background: Patients with breast cancer involve multiple decision support persons (DSPs) in treatment decision making, yet little is known about DSP engagement in decision making and its association with patient appraisal of the decision process. Methods: Patients newly diagnosed with breast cancer reported to Georgia and Los Angeles Surveillance, Epidemiology, and End Results registries in 2014‐2015 were surveyed 7 months after their diagnosis. The individual most involved in each respondent's decision making (the key DSP) was surveyed. DSP engagement was measured across 3 domains: 1) informed about decisions, 2) involved in decisions, and 3) aware of patient preferences. Patient decision appraisal included subjective decision quality (SDQ) and deliberation. This study evaluated bivariate associations with chi‐square tests between domains of DSP engagement and independent DSP variables. Analysis of variance and multivariable logistic regression were used to compare domains of DSP engagement with patient decision appraisal. Results: In all, 2502 patients (68% response rate) and 1203 eligible DSPs (70% response rate) responded. Most DSPs were husbands/partners or daughters, were white, and were college graduates. Husbands/partners were more likely to be more informed, involved, and aware (all P values < .01). English‐ and Spanish‐speaking Latinos had a higher extent of ( P = .02) but lower satisfaction with involvement ( P < .01). A highly informed DSP was associated with higher odds of patient‐reported SDQ (odds ratio, 1.46; 95% confidence interval, 1.03‐2.08; P = .03). A highly aware DSP was associated with higher odds of patient‐reported deliberation (odds ratio, 1.83; 95% confidence interval, 1.36‐2.47; P < .01). Conclusions: In this population‐based study, informal DSPs were engaged with and positively contributed to patients' treatment decision making. To improve decision quality, future interventions should incorporate DSPs. Abstract : According to this population‐based study using innovative methodology, informal decision support persons are engaged with and positively contribute to patients' treatment decision making. To improve decision quality, future interventions should incorporate decision support persons.